PENGARUH INTENSITAS MODAL DAN FINANCIAL PERFORMANCE TERHADAP TAX AVOIDANCE - Sisca Widya Prasasti; Adi Sofyana Latif (Jurnal Nusa Akuntansi, 2026)
This study aims to identify and examine the effect of capital intensity and financial performance on tax avoidance. A quantitative approach was used in this research, utilizing secondary data obtained from the companies annual financial statements during the period 2019–2023. The population in this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 87 companies. The research sample was selected using a purposive sampling method, resulting in 15 companies. The analysis methods used in this study include descriptive statistical analysis and panel data regression, assisted by EViews version 12 software. The results of the simultaneous test indicate that capital intensity and financial performance, when tested together, have a simultaneous influence on tax avoidance. Meanwhile, the partial test results show that capital intensity has no significant effect on tax avoidance, while financial performance has a significant effect on tax avoidance.